2013
DOI: 10.1080/15533174.2012.754768
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Co3O4 Cubic Structures and Evaluation of Their Catalytic Properties

Abstract: Co 3 O 4 cubic structures have been successfully prepared using the thermal decomposition of precursors approach. The precursor cubic structures were synthesized using a facile chemical precipitation method. X-ray diffraction, thermal gravimetric analysis, scanning electron microscopy, and UV-vis and infrared spectroscopy were used to characterize the products. The results showed that the reaction time and the nature of the surfactant played important roles in the formation of the products. The measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Cobalt sulfide finds widespread applications such as electrochemical conductivity [23, 24], electrochemical water splitting with photo anodes [25, 26], and supercapacitors with enhanced charge capacity and stability [27, 28]. On the other hand, tricobalt tetraoxide (Co 3 O 4 ) has been reported for use in supercapacitors, magnetic semiconductors [29, 30, 31], photocatalysis [32, 33], carbon monoxide (CO) and hydrocarbon oxidations, and other catalysis applications [34, 35, 36, 37, 38].…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt sulfide finds widespread applications such as electrochemical conductivity [23, 24], electrochemical water splitting with photo anodes [25, 26], and supercapacitors with enhanced charge capacity and stability [27, 28]. On the other hand, tricobalt tetraoxide (Co 3 O 4 ) has been reported for use in supercapacitors, magnetic semiconductors [29, 30, 31], photocatalysis [32, 33], carbon monoxide (CO) and hydrocarbon oxidations, and other catalysis applications [34, 35, 36, 37, 38].…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic role of Co 3 O 4 has been reported by many researchers. [28][29][30][31] Warang et al showed the photocatalytic efficiency of Co 3 O 4 for degradation of methylene blue via the photo-Fenton reaction. 28 Photocatalytic degradation of methyl violet in the presence of Co 3 O 4 catalysts has been reported by Li et al 29 Lou et al synthesized Co 3 O 4 nanorods, and studied photocatalytic degradation of different active dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] Warang et al showed the photocatalytic efficiency of Co 3 O 4 for degradation of methylene blue via the photo-Fenton reaction. 28 Photocatalytic degradation of methyl violet in the presence of Co 3 O 4 catalysts has been reported by Li et al 29 Lou et al synthesized Co 3 O 4 nanorods, and studied photocatalytic degradation of different active dyes. 30 In recent times, Pan et al have shown the photocatalytic performance of Co 3 O 4 nanostructured materials for the degradation of methyl orange.…”
Section: Introductionmentioning
confidence: 99%